Simulated delaminations in thermal NDT standards and the concept of thermally equivalent defects; NDT and E International; Vol. 151 - Vavilov V. P. Vladimir Platonovich; Burleigh D. D. Douglas; Chulkov A. O. Arseniy Olegovich; Kladov D. Dmitry (2025, 2025)
Title screen